Pattern-based framework for managing artificial intelligence innovation in scaled agile environments - Lukutin, O.; Лукутін, Олег Валерійович (ХНУРЕ, 2025)
This paper addresses the systemic challenges of integrating Artificial Intelligence (AI) into products within scaled Agile environments. It proposes a pattern-based organizational framework to manage the high uncertainty and complexity of AI projects. The framework introduces a dual-track system, utilizing a specialized best practices (patterns) AI Leading Team for discovery and Feature Teams for delivery, alongside a new AI Product Owner role. This process model offers a structured, de-risked approach on artificial intelligence (AI) in team management to managing innovation, ensuring development flow is maintained.
Keywords: artificial Intelligence